Imam Wahyu Beny Nugroho,David P Bahasa Indonesia - Nugroho, Imam Wahyu Beny; Arshy, David Permana; Yosita Elza Defitri; Wafiq Rifqi Abdul Wafi (Journal of Biobased Chemicals, 2024)
The high amount of banana consumption in Indonesia has caused banana peel waste to increase, which can cause environmental pollution. One of the utilization of banana peel waste is as a metal nanoparticle synthesis. This study aims to synthesize ZnO nanoparticles with banana peel extract as a capping agent and determine the effect of solvent volume variation on the characterization of ZnO particles using variable volume of ethanol-water solvent with a ratio of 2:1 and 1:1 (v/v). This research uses maceration extraction method for 24 hours. Characterization of ZnO particles was carried out including Fourier Transform Infrared Spectroscopy (FTIR) and Particle Size Analyzer (PSA). In this study, the total polyphenol and flavonoid content in ethanol - water 1:1 (v/v) horn banana peel extract was higher at 4.944% and 5.940% than ethanol - water 2:1 (v/v) at 4.114% and 4.131%. Based on the results of FTIR testing, both samples have ZnO peaks where in ethanol - water 1:1 (v/v), 441 cm-1 and 619 cm-1, while ethanol - water 2:1 (v/v) is 428 cm-1. Then, from the PSA test results, the ethanol-water 1:1 (v/v) sample has a smaller average nanoparticle diameter of 135.6 nm than the ethanol-water 2:1 (v/v) sample which is 153.6 nm. ZnO nanoparticles were successfully synthesized using the natural capping agent banana peel extract. Different levels of secondary metabolites in each extract have an influence on the diameter of the synthesized ZnO nanoparticles.